Increased circulating tumor DNA as a noninvasive biomarker of early treatment response in patients with metastatic ovarian carcinoma: A pilot study - Mariana Cartaxo Alves; Fernando Luiz Affonso Fonseca; Alayne Magalhães Trindade Domingues Yamada; Lílian Arruda do Rego Barros; André Lopes; Luana Carolina Ferreira Fiuza Silva; Ariana Sales Luz; Felipe José Silva Melo Cruz; Auro Del Giglio (Tumor Biology, 2020)
Detection of circulating tumor DNA is a new noninvasive technique with potential roles in diagnostic, follow-up, and prognostic evaluation of patients with many types of solid tumors. We aimed to evaluate the role of circulating tumor DNA in the setting of metastatic ovarian carcinoma. A prospective cohort of patients with metastatic ovarian cancer who were referred to systemic therapy was enrolled. Blood samples were collected before the start of treatment and monthly thereafter for 6 months. Circulating tumor DNA was quantified by real-time quantitative reverse transcription polymerase chain reaction of different lengths of Arthrobacter luteus elements as described by Umetani et al. A total of 11 patients were included, 2 for primary disease and 9 for recurrent disease. After the first cycle of chemotherapy, patients whose circulating tumor DNA levels increased from baseline were more likely to respond to chemotherapy than those whose circulating tumor DNA levels did not increase (p = 0.035). Furthermore, patients whose circulating tumor DNA levels rose after the first cycle of chemotherapy also had improved disease-free survival compared to those whose circulating tumor DNA levels did not increase (p = 0.0074). We conclude that the increase in circulating tumor DNA values collected in peripheral blood after the first cycle of systemic treatment in patients with advanced ovarian cancer is associated with an early response to systemic treatment and correlates with superior disease-free survival in this population. Circulating tumor DNA might be a specific, noninvasive, and cost-effective new biomarker of early response to systemic treatment in these patients.